ARCADIA-Kit with augmented reality application / Roslaili Anuar [et al.] - Anuar, Roslaili; Wan Zakaria, Wan Zamani; Othman, Noor Farhani; Zorkarnain, Siti Aisyah; Mohd. Reban, Nurul Liyana (2018)
The purpose of this study is to identify the efficient use of a developed product namely ARCADIA-KIT among Visual Arts Education (VAE) teachers. The study used the ADDIE model as a guideline to develop the product. Virtual Reality (VR) Application has been added to enhance the kit with the technology development to embrace the 21st Century classroom. The VR is the latest trend in teaching and learning in the classroom and is believed to be growing rapidly as is it more robust due to the virtual information embedded with the learning environment to create a realtime performance in the teaching and learning processes. With the growth of the Android and Smartphone among the users, the VR provided such an interesting platform for teaching as it can be accessed anywhere and anytime to ensure the teaching process to be delivered effectively. Quantitative method with questionnaire as a research instrument was used with selected respondents. The samples involved 60 Visual Art Education (VAE) teachers from selected schools in Shah Alam. Correlation analyses were carried out to determine the relationship between the variables studied. Data were analyzed using the Statistical Package for Social Sciences (SPSS) to obtain percentage and frequency. The findings indicate that the ARCADIAKit is efficient and useful for the teachers to use when teaching the Landscape topic